Zkušenost s výcvikem Point‑of‑Care ultrazvukového vyšetření srdce ve Fakultní nemocnici v Hradci Králové - Grenar, Petr; Nový, Jiří; Mědílek, Karel; Jakl, Martin (Vnitrni lekarstvi, 2023)
Emergency echocardiography is a reproducible method providing clinically significant information during the process of primary assessment of the acute cardiovascular diseases. The main aim of the course is implementation of the emergency echocardiography by non-cardiologist is the standardization of the procedure, structured training system and agreement on the competences. The article summaries the current training for non-echocardiographers in University Hospital Hradec Králové.
Keywords: akutní nemoc; Echocardiography; Hospitals; kardiovaskulární nemoci; ultrasound; ultrasonography; lidé; emergency medicine; echokardiografie; internal medicine; colchicine; nemocnice; echocardiography; Humans; Acute Disease; Cardiovascular Diseases